Agile software development practices that influence software quality: A review - Mohamed, Shafinah Farvin Packeer; Baharom, Fauziah; Deraman, Aziz; Yahya, Jamaiah (2011)
Agile software development (Agile) is being practiced in software industry nowadays as it fits the current business environment which focuses on delivering software to market as quickly as possible. In addition, Agile practitioners claim that it produces software with good quality.Thus, our research aims to identify Agile practices that should be followed in order to produce good quality software. Since many researchers report that the quality of people and process influence the quality of software product, this paper discusses on practices related to these two factors. The identified practices will be used for developing questionnaire in order to investigate current practice among Agile practitioners.